Cancer (Mantis) digitalis Herbst, 1793, an objective synonym of Oratosquillina quinquedentata (Brooks, 1886): neotype designation and reversal of precedence (Crustacea: Stomatopoda: Squillidae) - Ahyong, Shane T.; Low, Martyn E.y. (Zootaxa, 2013)
Johann Friedrich Wilhelm Herbst (1793) proposed two species-group names for stomatopod crustaceans from the East Indies (= Indonesia): Cancer (Mantis) arenarius (pp. 96–98, pl. 33, fig. 2) and Cancer (Mantis) digitalis (pp. 92–96, pl. 33, fig. 1) (Fig. 1A). Cancer (Mantis) arenarius Herbst, 1793, is a preoccupied objective synonym of what is now known as Lysiosquillina maculata (Fabricius, 1793) (see Low & Ng 2012: 47, 48).